GENETIC VARIATION OF WILD Musa acuminata COLLA FROM INDONESIA - Yuyu Suryasari Poerba; Diyah Martanti; Fajarudin Ahmad (SEAMEO BIOTROP, 2019)
Indonesia is the center of origin and diversity of Musa acuminata Colla, one of the progenitors of cultivated bananas today. However, the genetic variation of wild M. acuminata has not been studied extensively. Therefore, this study aimed to assess the genetic variation of Indonesian wild M. acuminata based on 10 RAPD (Random Amplified Polymorphic DNA) and 10 ISSR (Inter Simple Sequence Repeats) markers. The genetic properties of 17 populations of wild M. acuminata were analyzed using PopGene 1.32 based on Nei’s unbiased measures of genetic identity and genetic distance. Of the 443 DNA bands produced, 425 (95.94%) were polymorphic. Cluster analysis of the combined RAPD and ISSR data produced a dendrogram that separated the population of M. acuminata (A genome) from M. balbisiana (B genome), but not from M. schizocarpa (S genome). Nei’s genetic distance among the 17 populations of wild M. acuminata ranged from 0.03676 to 0.1634. The highest genetic distance was observed between M. acuminata var. rutilifes (from East Java) and M. acuminata var. sumatrana (from West Sumatra). The percentage of polymorphic loci among the 17 populations of M. acuminata ranged from 9.93% to 39.73%. Nei’s gene diversity (h) ranged from 0.0410 to 0.1418. The population of M. acuminata var. malaccensis displayed the highest genetic diversity among the 17 evaluated populations. The high level of genetic diversity of the wild M. acuminata from Indonesia highlights the importance of conservation and preservation of natural populations, as well as their potential use in banana breeding programs.